Valuing Water Resources in Turkey : A Methodological Overview and Case Study - World Bank Group (World Bank, Washington, DC, 2016)
Water is an essential component of Turkey’s economy and environment. Water resources are under strong pressure in terms of both quantity and quality.Freshwater productivity in Turkey is low compared to that of high-income countries,and of some upper middle-income countries of the region, such as Belarus, and Bosnia and Herzegovina, (World Bank, 2016). As the largest user of water, agriculture has extensive irrigation systems, however the existing irrigation practices are not very efficient.The Turkish government is considering a set of policy issues related to water resource management (WRM), including estimating the economic value of water and incorporating this into strategic decision-making on water allocation and pricing. There is a request for developing a tool for water valuation and accounting.The identification of water goods and services is based on the Total Economic Value (TEV) framework, which includes use and non-use values.The economic valuation of water benefits can be based on a wide range of valuation methods.The study presented in this report focused on water valuation with the objectives of introducing the concept and methods of water valuation, and demonstrating their use through actual application of valuation methods to Turkey’s water resources.A case study was quickly carried out in Beysehir Lake sub catchment, the largest freshwater lake in Turkey.The study further identified the need for the following actions: Nurture the political will and institutional arrangements to support the incorporation of valuation into decision-making.Adopt natural capital valuation and accounting as supporting tools in implementing the 2030 Agenda and delivering the Sustainable Development Goals (SDGs).Carry out in-depth valuation studies, covering a wider range of water values and river basins.Improve the valuation of water benefits in Beysehir Lake subcatchment through extended data collection and site-specific studies concerning the economic value of water uses (i.e. agricultural, municipal, recreational, and biodiversity).Develop national guidelines on water valuation and accounting to facilitate future studies and scale/implement existing efforts nationwide.The report contains six chapters. Following this introduction, Chapter two provides an overview of Turkey’s current water sector. Chapter three introduces the concept of total economic value, and Chapter four further discusses the valuation methods for each type of water use. To demonstrate the applicability of valuation in Turkey, Chapter five applies these methods to Beysehir Lake subcatchment in Konya Closed Basin, based on readily available information. Finally, Chapter six provides some conclusions and recommendations.